TPL-2 restricts Ccl24-dependent immunity to Heligmosomoides polygyrus. - Yashaswini Kannan; Lewis J Entwistle; Victoria S Pelly; Jimena Perez-Lloret; Alan W Walker; Steven C Ley; Mark S Wilson (PLoS Pathogens)
TPL-2 (COT, MAP3K8) kinase activates the MEK1/2-ERK1/2 MAPK signaling pathway in innate immune responses following TLR, TNFR1 and IL-1R stimulation. TPL-2 contributes to type-1/Th17-mediated autoimmunity and control of intracellular pathogens. We recently demonstrated TPL-2 reduces severe airway allergy to house dust mite by negatively regulating type-2 responses. In the present study, we found that TPL-2 deficiency resulted in resistance to Heligmosomoides polygyrus infection, with accelerated worm expulsion, reduced fecal egg burden and reduced worm fitness. Using co-housing experiments, we found resistance to infection in TPL-2 deficient mice (Map3k8-/-) was independent of microbiota alterations in H. polygyrus infected WT and Map3k8-/-mice. Additionally, our data demonstrated immunity to H. polygyrus infection in TPL-2 deficient mice was not due to dysregulated type-2 immune responses. Genome-wide analysis of intestinal tissue from infected TPL-2-deficient mice identified elevated expression of genes involved in chemotaxis and homing of leukocytes and cells, including Ccl24 and alternatively activated genes. Indeed, Map3k8-/-mice had a significant influx of eosinophils, neutrophils, monocytes and Il4GFP+ T cells. Conditional knockout experiments demonstrated that specific deletion of TPL-2 in CD11c+ cells, but not Villin+ epithelial cells, LysM+ myeloid cells or CD4+ T cells, led to accelerated resistance to H. polygyrus. In line with a central role of CD11c+ cells, CD11c+ CD11b+ cells isolated from TPL-2-deficient mice had elevated Ccl24. Finally, Ccl24 neutralization in TPL-2 deficient mice significantly decreased the expression of Arg1, Retnla, Chil3 and Ear11 correlating with a loss of resistance to H. polygyrus. These observations suggest that TPL-2-regulated Ccl24 in CD11c+CD11b+ cells prevents accelerated type-2 mediated immunity to H. polygyrus. Collectively, this study identifies a previously unappreciated role for TPL-2 controlling immune responses to H. polygyrus infection by restricting Ccl24 production.